World War II from above an aerial view of the global conflict - Harwood, Jeremy (Zenith Press, 2014)
"[The] story of the battle waged by Allied and Axis spies in the skies to obtain accurate aerial intelligence during the Second World War"--Page 4 of cover
Includes bibliographical references (pages 202-203) and index
Keywords: Geschichte 1900-2000; World War, 1939-1945 / Reconnaissance operations; World War, 1939-1945 / Aerial operations; Aerial reconnaissance / 20th century / History; Photographic interpretation (Military science) / History / 20th century; Photographic reconnaissance systems / History / 20th century; Geschichte; Weltkrieg (1939-1945); Zweiter Weltkrieg; Luftaufklärung; Luftkrieg; Bildband